THE DETERMINATION OF THE ARSENAL LOCATION IN AN EFFORT TO INCREASE THE CARRYING CAPACITY OF THE SEA FORCES IN CRITICAL AREAS OF THE NORTH NATUNA SEA - Kornia Adhi; Budisantoso; I Made Jiwa; Atiq Alfiansyah (Indonesian Naval Technology College STTAL, 2024)
The dynamics of the strategic environment in the North Natuna Sea area raises potential threat spots to the territory of the Republic of Indonesia where the Indonesian Navy needs to determine a marine security strategy where one of the things that must be prepared is the distribution of logistics in the form of musicians and weapons through the construction of the Arsenal warehouse. Through this research, an alternative strategic location as an Arsenal warehouse was determined as a storage place for ammunition supplies used to support KRI in carrying out operational tasks. Alternative locations for the construction of Arsenal are Lanal Bintan, Lanal Ranai Lanal Bangka Belitung and Lantamal IV Pontianak. Based on Perkasal No. 17 of 2008, the criteria used and are absolute requirements in determining the location are security, transportation access and supporting facilities. The data collection of this research was carried out using the questionnaire distribution method and conducting interviews with experts. The Delphi method is used in this research to determine and agree on relevant and valid criteria and sub-criteria to be researched to the next stage. Furthermore, the Analytic Network Process (ANP) method is used to determine the best alternative by processingdata using Super Decision Software. The results of this study were obtained The priority of the alternative location of the Arsenal warehouse is Lanal Bintan with a weight value of 0.536308.